ZEQoS: A New Energy and QoS-Aware Routing Protocol for Communication of Sensor Devices in Healthcare System. (5th June 2014) - Khan, Zahoor Ali; Sivakumar, Shyamala; Phillips, William; Robertson, Bill
Abstract : This paper proposes a novel integrated energy and QoS-aware routing protocol with the considerations of energy, end-to-end latency, and reliability requirements of body area network (BAN) communication. The proposed routing protocol, called ZEQoS, introduces two main modules (MAC layer and network layer) and three algorithms (neighbor table constructor, routing table constructor, and path selector). To handle ordinary packets (OPs), delay-sensitive packets (DSPs), and reliability-sensitive packets (RSPs), the new mechanism first calculates the communication costs, end-to-end path delays, and end-to-end path reliabilities of all possible paths from a source to destination. The protocol then selects the best possible path(s) for OPs, RSPs, and DSPs by considering their QoS requirement. Extensive simulations using OMNeT++ based simulator Castalia 3.2 demonstrate that the performance of the proposed integrated algorithm is satisfactory when tested on a real hospital scenario, and all data types including OPs, DSPs, and RSPs are used as offered traffic. Simulations also show that the ZEQoS also offers better performance in terms of higher throughput, less packets dropped on MAC and network layers, and lower network traffic than comparable protocols including DMQoS and noRouting.